Koh Catalyst Concentration and Stirring Speed in The Transesterification Process on Biodiesel Yield from Spent Coffee Grounds Oil - Desi Heltina; Fadrian Oktori; Amun Amri; Agustina Dumaria; Maria Peratenta Sembiring (Universitas Pendidikan Ganesha, 2026)
Coffee grounds have a fairly high oil content in the seeds of around 15-20% which has great potential to be used as raw material for making biodiesel. This study aims to determine the physical characteristics of coffee grounds biodiesel; and to determine the effect of stirring speed, amount of catalyst and reaction time on the yield of coffee grounds biodiesel. The type of research on biodiesel production from coffee grounds waste is quantitative. The data collection method is carried out by experimenting on biodiesel that has been obtained from coffee grounds waste oil on the concentration of KOH catalyst, stirring speed and reaction time. After the required data has been collected, an analysis is carried out using a descriptive and analytical case study method. The result of the study obtained the best condition, namely at a KOH catalyst concentration of 3% wt oil, and a stirring speed of 800 rpm, a biodiesel yield of 30,19%. So it can be concluded that coffee grounds oil biodiesel has been successfully obtained and has met the quality standards of ASTM D6751 and EN 14214. The yield of biodiesel produced increased along with the increasing transesterification reaction time. GC-MS analysis showed that coffee grounds oil biodiesel was mostly composed of linoleic acid and palmitic acid. The implications of this research can be used in the development of further research related to innovations in improving environmentally friendly fuels based on organic waste.